Peer-supported self-management for people discharged from a mental health crisis team: a randomised controlled trial. Issue 10145 (4th August 2018) - Johnson, Sonia; Lamb, Danielle; Marston, Louise; Osborn, David; Mason, Oliver; Henderson, Claire; Ambler, Gareth; Milton, Alyssa; Davidson, Michael; Christoforou, Marina; Sullivan, Sarah; Hunter, Rachael; et al.
Summary: Background: High resource expenditure on acute care is a challenge for mental health services aiming to focus on supporting recovery, and relapse after an acute crisis episode is common. Some evidence supports self-management interventions to prevent such relapses, but their effect on readmissions to acute care following a crisis is untested. We tested whether a self-management intervention facilitated by peer support workers could reduce rates of readmission to acute care for people discharged from crisis resolution teams, which provide intensive home treatment following a crisis. Methods: We did a randomised controlled superiority trial recruiting participants from six crisis resolution teams in England. Eligible participants had been on crisis resolution team caseloads for at least a week, and had capacity to give informed consent. Participants were randomly assigned to intervention and control groups by an unmasked data manager. Those collecting and analysing data were masked to allocation, but participants were not. Participants in the intervention group were offered up to ten sessions with a peer support worker who supported them in completing a personal recovery workbook, including formulation of personal recovery goals and crisis plans. The control group received the personal recovery workbook by post. The primary outcome was readmission to acute care within 1 year. This trial is registered with ISRCTN, number 01027104. Findings: 221 participants were assigned to the intervention group versus 220 to the control group; primary outcome data were obtained for 218 versus 216. 64 (29%) of 218 participants in the intervention versus 83 (38%) of 216 in the control group were readmitted to acute care within 1 year (odds ratio 0·66, 95% CI 0·43–0·99; p=0·0438). 71 serious adverse events were identified in the trial (29 in the treatment group; 42 in the control group). Interpretation: Our findings suggest that peer-delivered self-management reduces readmission to acute care, although admission rates were lower than anticipated and confidence intervals were relatively wide. The complexity of the study intervention limits interpretability, but assessment is warranted of whether implementing this intervention in routine settings reduces acute care readmission. Funding: National Institute for Health Research.